#TITLE_ALTERNATIVE# - ABDURRAHMAN (NIM: 12914008), UMAR
The aim of this study was to estimate sediment transport rate at Karangsong Beach, Indramayu by using beach evolution model. The model was applied to analyze significant coastal morphological change due to the effects of the jetty construction in 2005. Depth of closure, i.e., depth where the coastal profile is unchanged, and shoreline change calculation was required to use this model. Shoreline change was obtained from Google Earth satellite image analysis. Meanwhile, depth of closure was calculated using annual mean and standard deviation of significant wave height by using SWAN wave model with 1 ÃƒÂ— 1 km resolution. According to this study, the beach evolution model resulted in a difference of 7,5% compared to calculation of coastal volume change. The largest total coastal area and total shoreline change occurred between 2001 and 2008 with the value 297.136 m2 and 13.897 m respectively. The results of sediment transport calculations show different patterns between northern and southern areas of the jetty due to the presence of structure. In addition, sediment transport rate showing fluctuation value which decrease over time indicate natural processes to reach the equilibrium condition after construction of the jetty.